The problem of attainment to the dietary changes of hypertension in the context of Primary Health Care - Luciana Saraiva da Silva; Rosângela Minardi Mitre Cotta; Andréia Queiroz Ribeiro; Amanda Gomes Ribeiro (O Mundo da Saúde)
Systemic arterial hypertension (SAH) is a serious public health problem in the world. Changes in lifestyle are considered fundamental in the prevention and control of hypertension, which can be achieved through health education actions at the level of primary care. The aim of this study was to evaluate the effect of two strategies of nutrition and health education for the orientation of dietary changes indicated in the treatment of SAH. The study was conducted with women having hypertension (n = 27) in the city of Porto Firme-MG. The intervention consisted in: 1) educational group activities (G1, n = 14); 2) educational group activities and household guidelines (G2, n = 13). The study evaluated the evolution of anthropometric, biochemical, clinical and dietetic parameters in three stages: T1 - before the intervention, T2 – at the end of the intervention and T3 - eight months after interventions stopped. In group 1, there was no statistically significant differences in the parameters, while in group 2 there was statistically significant differences for the values of waist circumference (p = 0,030), systolic blood pressure (p = 0,012) and consumption of salt (p = 0,003). While they were instructed, the women followed the dietary guidelines which positively influenced the parameters from T1 to T2. In T3, it was observed that the changes were not incorporated in their lifestyle